Highly hydrogenated graphene through microwave exfoliation of graphite oxide in hydrogen plasma : towards electrochemical applications - Eng, Alex Yong Sheng (2014)
Hydrogenated graphenes exhibit a variety of properties with potential applications in devices, ranging from a tunable band gap to fluorescence, ferromagnetism, and the storage of hydrogen. We utilize a one-step microwave-irradiation process in hydrogen plasma to create highly hydrogenated graphene from graphite oxides. The procedure serves the dual purposes of deoxygenation and concurrent hydrogenation of the carbon backbone. The effectiveness of the hydrogenation process is investigated on three different graphite oxides (GOs), which are synthesized by using the Staudenmaier, Hofmann, and Hummers methods. A systematic characterization of our hydrogenated graphenes is performed using UV/Vis spectroscopy, SEM, AFM, Raman spectroscopy, FTIR spectroscopy, X-ray photoelectron spectroscopy (XPS), combustible elemental analysis, and electrical conductivity measurements. The highest hydrogenation extent is observed in hydrogenated graphene produced from the Hummers-method GO, with a hydrogen content of 19 atomic % in the final product. In terms of the removal of oxygen groups, microwave exfoliation yields graphenes with very similar oxygen contents despite differences in their parent GOs. In addition, we examine the prospective application of hydrogenated graphenes as electrochemical transducers through a cyclic voltammetry (CV) study. The highly hydrogenated graphenes exhibit fast heterogeneous electron-transfer rates, suggestive of their suitability for electrochemical applications in electrodes, supercapacitors, batteries, and sensors.